Cálculo dinâmico para adição de cálcio silício para aço microligado ao cromo e molibdênio - Marcelo Fernandes Mercier (2014)
The presence of inclusions in the steel is directly associated to its cleanliness. Different types of non-metallic inclusions can harm the manufacturing and forming processes as well as the final steel properties demanded for its application. Inclusions are formed and modified throughout the steel manufacturing process, and their characteristics are mainly related to the techniques of secondary refining and continuous casting employed. In the present work, the relationship between the steel deoxidation (total oxygen content) and the amount of calcium added was studied and evaluated aiming at appropriate castability and improved steel cleanliness. With this focus, a methodology to evaluate the CaSi additions depending on the calcium yield, total oxygen, chemical composition and temperature of the molten steel (dynamic addition) was developed, aiming at improving the steel cleanliness. The results of the experiments using the dynamic addition method developed showed an improvement the steel cleanliness with the formation of liquid inclusions, when compared to the results adopting normal practice of calcium addition.